Update cerebellum and cognition - Jacobi, Heike; Faber, Jennifer; Timmann-Braun, Dagmar; Klockgether, Thomas (Journal of neurology, 2021)
There is now robust evidence that the cerebellum—apart from its well-established role in motor control—is crucially involved in a wide spectrum of cognitive and affective functions. Clinical and neuropsychological studies together with evidence from anatomical studies and advanced neuroimaging have yielded significant insights into the specific features and clinical relevance of cerebellar involvement in normal cognition and mood.